Transgenic soybean harboring Isopentenyl transferase 10 (GmIPT10) displays improved drought resilience - Thi Hoang, Xuan Lan; Phuong Thao, Nguyen (Academia Journal of Biology, 2026)
Soybean (Glycine max (L.) Merrill) is an important global source of plant-based oil and nutrition yet is highly sensitive to water deficit conditions, which significantly impair its growth, development and productivity. In this study, transgenic soybean lines carrying a soybean cytokinin metabolic gene Isopentenyl transferase (GmIPT10), which was previously identified as a drought-associated gene, were evaluated for their resilience under drought stress conditions. Following the water withholding treatments at the vegetative and early flowering stages, the transgenic plants exhibited reduced stress indicators compared with the control counterparts, including approximately 27−51% lower malondialdehyde (MDA) levels and 33−55% less cellular ion leakage in the leaf tissues. Under the adverse conditions, RT-qPCR analysis revealed elevated expression levels of several drought-responsive marker genes (GmRD20A, GmERD1) and antioxidant-related genes (GmPOD, GmCAT, GmST4) but more suppressed expression in the photosynthesis-negative regulator GmSGR1 in the transgenic plants. Additionally, the transformants maintained a higher proportion of mature pods containing two or three seeds, indicating enhanced yield potential under stress. Collectively, these findings suggest a better stress tolerance of IPT-transgenic soybeans, which is partially achieved by better plant protection from drought-induced damages, especially enhanced defense against oxidative stress, thereby supporting plant functions under water-limited conditions. This research highlights the biotechnological potential of the soybean GmIPT10 gene in enhancing soybean tolerance and its productivity under water stress conditions.